Bird diversity in Mangrove areas in Tumpat, Kelantan - Mohamad Asri, Nur Syuhada; Hambali, Kamarul; Amir, Aainaa; Norazlimi, Nor Atiqah (The Malayan Nature Journal (MNJ), 2020)
Mangroves forests play an important role in the management of coastal ecosystem of Malaysia. However, day by day, the number of mangroves is reduced due to the high demand for aquaculture, industrials development, and urbanization. The objective of this study is to determine the comparison of bird diversity between waterbird and terrestrial bird at mangrove area in Tumpat, Kelantan by using the point count method. 256 individuals were recorded representing 38 species and 23 families from the study. Out of the total, 27 species (202 detections, 78.91%) and 11 species (54 detections, 21.09%) belong to terrestrial bird and waterbird respectively. From the result analysis, the highest detection for the terrestrial bird were Yellow-vented Bulbul (Pycnonotus goaivier) (49 detections) while the lowest were Lesser Coucal (Centropus bengalensis) (1 detection). Little Egret (Egretta garzetta) (13 detections) is the highest detection for waterbird while the lowest is Black-crowned Night Heron (Nycticorax nycticorax) (1 detection). Terranestrial birds recorded the highest diversity (H’= 2.90), species richness (Margalef’s= 5.09), and evenness (0.87). The results of this study signified that the mangrove area in Tumpat is an important habitat for waterbirds as well as the terrestrial bird.